2001
DOI: 10.1016/s0025-7125(05)70374-6
|View full text |Cite
|
Sign up to set email alerts
|

Postoperative Delirium

Abstract: Delirium is a common postoperative complication that is associated with substantial patient morbidity and mortality. Because of the variability in its presentation, delirium has the potential to be overlooked or misdiagnosed. There are few well-designed prospective studies looking at the incidence of delirium; however, retrospective data reveal it to be highly variable. The cause is multifactorial, with the largest predisposing factors being patient age, cerebral disease, and poor preoperative medical status. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
0
4

Year Published

2002
2002
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 48 publications
(19 citation statements)
references
References 14 publications
2
13
0
4
Order By: Relevance
“…Previous studies reported the efficacy of risperidone for the treatment of delirium [14,42,44]. In our study, 21 patients with delirium were treated with risperidone.…”
Section: Discussionmentioning
confidence: 87%
“…Previous studies reported the efficacy of risperidone for the treatment of delirium [14,42,44]. In our study, 21 patients with delirium were treated with risperidone.…”
Section: Discussionmentioning
confidence: 87%
“…Apart from a multifaceted interdisciplinary approach involving environmental strategies, antipsychotic medication remains the cornerstone of treatment (1). Among these drugs, the typical antipsychotic haloperidol has been the drug of choice, mainly owing to its lack of anticholinergic (1) and minimal hemodynamic and respiratory side effects (2). Over the last decade, however, evidence has emerged for the use of second generation antipsychotics like risperidone-but only in the form of case reports and case series (3,4).…”
Section: Effectiveness Of Risperidone In Deliriummentioning
confidence: 99%
“…Several risk factors for delirium have been elucidated: infection, hypoxia, myocardial ischemia, metabolic derangements, hypoalbuminemia, electrolyte disturbance, and metastatic brain tumor. 4,10,11 These are systemic etiologic factors rather than local factors. In the present study, surgery for malignant tumors of digestive organs such as the stomach, liver, colon, and pancreas was strongly associated with LRT, especially in men.…”
Section: Discussionmentioning
confidence: 99%